Rethinking conventional and Islamic economics: An integrated conceptual framework for addressing contemporary socio-economic challenges - Vina Rahayu Chairunnisa; Amirul Bakhri (Societa: Journal of Society and Change, 2026)
Although the differences between conventional and Islamic economics have been widely examined, the conceptual relationships among paradigms, development goals, economic instruments, public policy, and responses to contemporary socio-economic challenges remain insufficiently integrated. This study comparatively examines how conventional and Islamic economics respond to contemporary socio-economic challenges by developing a systematic conceptual framework. It employs a qualitative approach using a conceptual paper design based on library research, with data analyzed through comparative qualitative analysis and thematic analysis. The findings demonstrate that the differing responses of the two economic systems originate from their underlying paradigms, which shape development goals, economic instruments, and public policy orientations. Conventional economics emphasizes market efficiency and economic growth, whereas Islamic economics integrates economic efficiency with distributive justice, social responsibility, and ethical values. This study contributes by proposing an integrated conceptual framework that clarifies the interrelationships among these dimensions in explaining how both economic systems respond to contemporary socio-economic challenges. Abstrak Perbedaan paradigma antara ekonomi konvensional dan ekonomi Islam telah banyak dikaji. Namun, hubungan konseptual antara paradigma, tujuan pembangunan, instrumen ekonomi, kebijakan publik, dan respons terhadap tantangan sosial-ekonomi kontemporer masih belum dijelaskan secara terpadu. Penelitian ini bertujuan menganalisis secara komparatif respons ekonomi konvensional dan ekonomi Islam terhadap tantangan sosial-ekonomi kontemporer melalui pengembangan kerangka konseptual yang sistematis. Penelitian ini menggunakan pendekatan kualitatif dengan desain conceptual paper berbasis library research, yang dianalisis melalui comparative qualitative analysis dan thematic analysis. Hasil penelitian menunjukkan bahwa perbedaan respons kedua sistem ekonomi berakar pada paradigma yang membentuk tujuan pembangunan, instrumen ekonomi, dan arah kebijakan publik. Ekonomi konvensional menitikberatkan efisiensi pasar dan pertumbuhan ekonomi, sedangkan ekonomi Islam mengintegrasikan efisiensi ekonomi dengan keadilan distributif, tanggung jawab sosial, dan nilai-nilai etika. Penelitian ini memberikan kontribusi melalui pengembangan kerangka konseptual terpadu yang memperjelas hubungan antarkomponen dalam menjelaskan respons kedua sistem ekonomi terhadap tantangan sosial-ekonomi kontemporer.